Evidence-based treatment of anorexia nervosa. - Fairburn, C (2005)
This paper addresses the question "Is evidence-based treatment of anorexia nervosa possible?" "Barely" is the conclusion drawn. New forms of treatment are needed for adults with anorexia nervosa, and the true value of family-based treatment for adolescents has yet to be established.